Peningkatan Hasil Belajar Melalui Kemandirian Belajar Dan Komunikasi Interpersonal Di Sekolah Minggu Buddha (SMB) Chong De Se-Sumatera Utara - Muljadi Muljadi; Srie Muldrianto; Lida (Dhammavicaya : Jurnal Pengkajian Dhamma, 2022)
The purpose of this study was to determine the independence of learning and interpersonal communication on the learning outcomes of Chong-De High School students in North Sumatra. The independent variable in this study is learning independence and interpersonal communication and the dependent variable is learning outcomes. In this study using a sample using probability sampling technique, with a total sample of 150 respondents. This research uses primary data, data is collected by distributing questionnaires to respondents via google form which is tested with SPSS 20.0 for Windows. The results of the research show that learning independence has a positive effect on student learning outcomes of SMB Chong- De North Sumatra with the resulting correlation coefficient of ry1 = 0.790 and the resulting coefficient of determination score of r2y1 = 0.624. Interpersonal communication has a positive effect on student learning outcomes of SMB Chong-De North Sumatra with the resulting correlation coefficient of ry2 = 0.589 and the resulting coefficient of determination score of r2y2 = 0.347. Independent learning and interpersonal communication have a positive and significant effect jointly on student learning outcomes of SMB Chong-De North Sumatra with a correlation coefficient score of ry1,2 = 0.815 and a coefficient of determination score of r2y1,2 = 0.665. The regression equation in this study is as follows: 1.2 = 12,471 + 0.685X1 + 0.234X2. Based on these results, to optimize student learning outcomes, it is necessary to have policies and regulations to increase learning independence and interpersonal communication.